Special education international perspectives biopsychosocial, cultural, and disability aspects - Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2014)
The volume will be divided into four parts. Part 1 will present an overview on disability that focuses on two major themes, namely, the biopsychosocial approaches to disability and cultural views of disability. Part 2 will examine five major areas of high incidence exceptionalities: cognitive impairment, learning disabilities and attention deficit hyperactivity, autism spectrum disorders, behavioural/emotional disorders and speech and language disorders.
Biopsychosocial approaches to understanding disability : building connections: how teachers matter / Sandra Burkhardt -- Diversity and disability / Sandra Burkhardt -- Cognitive impairment and intellectual disability / Michael L. Wehmeyer ... [et al.] -- Students with learning disabilities and attention deficit hyperactivity disorders / Jeffrey P. Bakken, Stephanie Gaddy -- Autism spectrum disorders : the worldwide charm and challenge of autism spectrum disorders / Emily Boshkoff Johnson -- International perspectives on emotional and behavioral disorders / Frederick J. Brigham -- Speech and language impairments / Satasha L. Green, Kimberly M. Edwards -- Technological advances in special education / Emily C. Bouck, Sara Flanagan.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Special education